Dual effect of cobra cardiotoxin on vascular smooth muscle and endothelium - Ho Kwet-Heung; Kwan Chiu-Yin; Huang Shou-Jian; Bourreau Jean-Pierre (Acta Pharmacologica Sinica; Vol 19, No 3 (May 1998): Acta Pharmacologica Sinica, 2016)
AIM: To assess the cytotoxic effects of cobra cardiotoxin (CTX) on rat aorta. METHODS: Measure of contractility of aortic rings with or without endothelium. RESULTS: In endothelium-intact rings, CTX 10 mumol.L-1 induced a transient relaxation followed by a sustained contraction. Removal of the endothelium or pre-incubation of the rings with NO synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME) abolished the transient relaxation but did not affect the magnitude of the contractile response induced by CTX. CTX itself induced contraction of vascular smooth muscle but also reduced contractions induced by phenylephrine (PhE) or KCl stimulation in a concentration-dependent manner. Contraction induced by CTX was dependent on the external Ca2+ concentration. Maximal contractile response to CTX was obtained in medium containing Ca2+ 1 mmol.L-1. This response decreased with higher Ca2+ concentration and disappeared when Ca2+ 7 mmol.L-1, organic and inorganic calcium channel blockers were present in the external solution before CTX addition. In preparations with the endothelium intact and incubated with CTX, relaxation by acetylcholine (ACh) stimulation of the tension induced by PhE was decreased. Endothelium-dependent relaxation to ACh was preserved when Ca2+ 5 mmol.L-1 was added to the medium prior to CTX. CONCLUSION: CTX first triggers the release of NO from the endothelium which results in muscle relaxation, and then causes smooth muscle contraction, Ca2+ and Ca2+ channel blockers prevented the effect of CTX.